Perancangan dan Implementasi Sistem Manajemen Inventory Barang Berbasis CRUD Menggunakan Metode Waterfall - Nikodemus Christiano David; Bintang Putra Aryatama; Muh Rizky Anggara Yunan Putra; Firman Andriyanto Arief; Riyan Abdul Aziz (Jurnal Riset Multidisiplin Edukasi, 2025)
Efficient inventory management is crucial for company operations, especially in today's digital era. The implementation of an inventory management system based on CRUD (Create, Read, Update, Delete) offers a structured solution for managing stock, allowing users to easily add, view, update, and delete inventory data. This system enhances efficiency and accuracy in stock record-keeping but still has limitations, such as the lack of advanced automation features and more complex data analysis. This study evaluates the benefits and challenges of implementing the CRUD system and provides guidelines for further development to ensure the system meets the evolving operational needs. In conclusion, while the system is effective, adjustments and enhancements are needed to improve its scalability and flexibility in the future.